Influence Audit Fee, Tenure Audit And KAP Rotation On Audit Quality: Empirical Study on BUMN Banking in Indonesia - Nurcahyani, Widy; Ramli, Abdul Haeba; Larasati, Ayu; Reza, Heru Kreshna (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
The purpose of this research is to prove that the influence audit fees, KAP rotation, and tenure audit on the quality of audits of state-owned banking staff located in Indonesia. This research consists of three independent variables consisting of audit fees, audit tenure, and KAP rotation, as well as one dependent variable, namely audit quality. This research uses a methodology causal explanatory, causal explanatory research that involves explaining the relationships between variables and evaluating previously created hypotheses. In this research, there are 4 companies and research objects in State-Owned Enterprise (BUMN) banking companies listed on the Indonesia Stock Exchange (BEI) during the 2015-2022 period. The data analysis technique in this research uses statistical data. The results of this research show that simultaneously audit fees, tenure audit, and KAP rotation has a positive influence on audit quality. Further more audit fees has a positive effect on audit quality. Then tenure audit has a positive effect on audit quality. Meanwhile, KAP rotation has a positive influence on audit quality.   Keywords : Fees Audit, Audit Tenure, KAP Rotation, and Audit Quality